2014
DOI: 10.1371/journal.pone.0114608
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Growth Conditions from Internal Metabolic Fluxes in an In-Silico Model of E. coli

Abstract: A widely studied problem in systems biology is to predict bacterial phenotype from growth conditions, using mechanistic models such as flux balance analysis (FBA). However, the inverse prediction of growth conditions from phenotype is rarely considered. Here we develop a computational framework to carry out this inverse prediction on a computational model of bacterial metabolism. We use FBA to calculate bacterial phenotypes from growth conditions in E. coli, and then we assess how accurately we can predict the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
(31 reference statements)
0
18
0
Order By: Relevance
“…For instance, Sridhara and colleagues investigated whether bacterial growth conditions could be inferred from intracellular flux configurations [67]. Multinomial logistic regression was used in conjunction with least absolute shrinkage and selection operator (LASSO) regularization to relate growth conditions to simulated metabolic fluxes.…”
Section: Supervised Fluxomic Analysismentioning
confidence: 99%
“…For instance, Sridhara and colleagues investigated whether bacterial growth conditions could be inferred from intracellular flux configurations [67]. Multinomial logistic regression was used in conjunction with least absolute shrinkage and selection operator (LASSO) regularization to relate growth conditions to simulated metabolic fluxes.…”
Section: Supervised Fluxomic Analysismentioning
confidence: 99%
“…This fluxomic data can be trained directly through ML methods to obtain more biological insight into the desired system (Figure 5A). [ 129,130 ] (b) ML is an effective tool for merging and analyzing heterogeneous omics datasets beyond ML applications to single omics. [ 131 ] By combining these multi‐omics datasets with GEMs, context‐specific models are generated.…”
Section: Synergisms Of Cbm and MLmentioning
confidence: 99%
“…For this reason, the prediction conducted using a simple linear regression. The results showed that using the intracellular flux values, carbon and nitrogen sources utilized in the initial culture medium could be predicted even with a small number of impurities [114]. In a recent study, Oyetunde et al extracted over 1,200 curated bioprocess datasets from 100 articles to predict microbial factories' performance (yield, titer, and rate).…”
Section: Instances Of Cbm Coupled With ML For Fermentation Analysis and Optimizationmentioning
confidence: 99%